2005
DOI: 10.1657/1523-0430(2005)037[0297:sospms]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Succession on Subalpine Placer Mine Spoil: Effects of Revegetation with Alnus viridis, Alaska, U.S.A

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…Also, growth of the Frankia-alders caused a decrease in the soil pH. Similar results were found with alders growing on gold mine tailings (Densmore, 2005). Van Miegroet and Cole (1985) suggested that the decrease in pH seen in alder stands could be linked to nitrification processes associated with nitrogen fixation.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Also, growth of the Frankia-alders caused a decrease in the soil pH. Similar results were found with alders growing on gold mine tailings (Densmore, 2005). Van Miegroet and Cole (1985) suggested that the decrease in pH seen in alder stands could be linked to nitrification processes associated with nitrogen fixation.…”
Section: Discussionsupporting
confidence: 72%
“…In the long-term, this could bring a new nitrogen source into the system, with increased biomass producing a flow-on effect to eventually increase organic matter and nutrients in the surrounding soil (Pérez-Corona et al, 2006). This nitrogen could facilitate the growth of other tree species and the establishment of multi-storey vegetation (Kohls et al, 2003;Densmore, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the planting of structural dominants may be a means of facilitating the entry of other native species into a community, either because these species compete successfully with exotic species that currently occupy the site or because they generate conditions that facilitate recruitment of other native species. Use of shrubs or trees as nurse plants has been a commonly used method of vegetation restoration in semi-arid (Maestre et al 2001;Gasque & García-Fayos 2004;Blignaut & Milton 2005;Huber-Sannwald & Pyke 2005), montane-Mediterranean (Castro et al 2002;Gómez-Aparicio et al 2004), tropical-forest (Sánchez-Velásquez et al 2004) and mine-site (Densmore 2005;Frérot et al 2006) environments.…”
Section: Introductionmentioning
confidence: 99%
“…Without active ecosystem enhancement, former placer mining sites located in the Klondike were found to take approximately 20 years to establish shrub thickets/communities, and full recovery to a coniferous forest required over 80 to 100 years (Entrix, 1986). The use of reclamation practices aimed at accelerating ecosystem recovery can reduce the amount of time needed for a shrub thicket/community to establish to less than ten years from initiation of the reclamation process (Entrix, 1986;Densmore, 2005). Similarly, topsoil replacement and tree planting has resulted in successful plant community reconstruction within 12 to 15 years of oil shale mining in Estonia, although floristic richness, soil nutrients and organic matter accumulation continue to increase over time and differ between sites planted to birch and sites planted to pine (Laarmann, 2015).…”
Section: Factors Affecting Ecosystem Recoverymentioning
confidence: 99%
“…has been found to boost soil nitrogen content in floodplain substrates (Rhoades et al, 2008). In a ten-year study in Alaska, Alnus viridis (Chasix) DC was planted on abandoned placer mining sites, where it facilitated improved growth and vigour of associated Salix alaxensis (Andersson) Coville and Populus balsamifera L. plants (Densmore, 2005).…”
Section: Factors Affecting Ecosystem Recoverymentioning
confidence: 99%